(untitled) (Journal of the College of Basic Education, 2023)
The Strait of Hormuz is one of the most important straits and waterways in the world, as it connects the Arabian Gulf on the one hand, and the Gulf of Oman, the Arabian Sea, and the Indian Ocean on the other. Therefore, it is considered the only sea outlet for countries bordering the Arabian Gulf only, such as Iraq, Kuwait, Bahrain, and Qatar. It is also the port President of each of the Kingdom of Saudi Arabia, which overlooks the Gulf in the east and the Red Sea in the west, and of the United Arab Emirates, which overlooks the Arabian Gulf and the Gulf of Oman, and the Sultanate of Oman, which overlooks the Arabian Gulf, the Gulf of Oman, and the Arabian Sea, and Iran, which overlooks the Arabian Gulf, the Gulf of Oman, and the Arabian Sea .Its strategic importance stems from its being a transit point for 35 to 40% of the world’s seaborne oil.